ChemInform Abstract: A Unified Approach to Pyrrole‐Embedded Aza‐Heterocyclic Scaffolds Based on the RCM/Isomerization/Cyclization Cascade Catalyzed by a Ru/B‐H Binary Catalyst System. Issue 34 (4th August 2016) - Inamdar, Suleman M.; Chakrabarty, Indradweep; Patil, Nitin T.
Abstract: The title compounds are prepared by a cascade reaction sequence of (pyrrolylphenyl)allylacrylamides using Hoveyda‐Grubbs II/BINOL hydrogen phosphate as catalyst.